LEVEL OF RESPONSIBILITY OF THE ACCOUNTING PROFESSIONAL TO THE TAXPAYER - Caballero Benítez, Carlos; David Carneiro Vera, Augusto; Rodrigo Núñez Escobar, Evan (Revista Gênero e Interdisciplinaridade, 2023)
Level of responsibility of the accounting professional towards the taxpayer. The Nature of the investigation is of a quantitative type, it focuses on measuring the opinion of accounting professionals, knowing the norms and laws that affect it when breaking professional ethics, not complying with the true profile of an accountant, since in any modality of tribute is directly affected. For both subjects, it represents an enormous responsibility, mainly for the taxpayer, since it is his name and business that is at stake when carrying out improper maneuvers. It is mandatory that by not having sufficient knowledge in the execution of the accounting work and operation, it would negatively affect the both involved since there are sanctions and consequences.